Atypical Facial Emotion Recognition in Children with Autism Spectrum Disorders: Exploratory Analysis on the Role of Task Demands. (September 2021) - Nagy, Emese; Prentice, Louise; Wakeling, Tess
People with autism spectrum disorders (ASDs) have difficulty with socio-emotional functioning; however, research on facial emotion recognition (FER) remains inconclusive. Individuals with ASD might be using atypical compensatory mechanisms that are exhausted in more complex tasks. This study compared response accuracy and speed on a forced-choice FER task using neutral, happy, sad, disgust, anger, fear and surprise expressions under both timed and non-timed conditions in children with and without ASD ( n  = 18). The results showed that emotion recognition accuracy was comparable in the two groups in the non-timed condition. However, in the timed condition, children with ASD were less accurate in identifying anger and surprise compared to children without ASD. This suggests that people with ASD have atypical processing of anger and surprise that might become challenged under time pressure. Understanding these atypical processes, and the environmental factors that challenge them, could be beneficial in supporting socio-emotional functioning in people ASD.